The role of rumah budaya kratonan in local cultural preservation as a form of civic engagement - Emilia Novitasari; Yudi Ariana; Anis Suryaningsih (Institute of Computer Science (IOCS), 2026)
This study aims to: (1) describe the role of the Kratonan Cultural House in preserving local culture as a form of civic engagement, and (2) identify the obstacles and challenges faced by the Kratonan Cultural House in preserving local culture. This study uses a qualitative research method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. The sampling technique used purposive sampling. Data analysis used the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. Data validity testing techniques used source triangulation and method triangulation. The results of the study indicate that the Kratonan Cultural House plays a role as: (1) a cultural learning space through the Surakarta History Gallery, educational tours, and arts and culture classes; (2) a creative space through organizing workshops, seminars, cultural discussions, and art performances; and (3) a forum for community participation through active community involvement in cultural preservation activities that reflect civic engagement. These roles are able to increase public awareness of the importance of preserving local culture, strengthen collaboration between communities, and encourage cross-generational cultural inheritance. The obstacles faced by the Kratonan Cultural House include: (1) limited human resources, especially in the field of promotion and management of information on cultural activities, and (2) facilities and infrastructure that do not fully support the implementation of cultural activities. Meanwhile, the challenges faced include: (1) the strong influence of foreign culture which is increasingly easily accessible to the younger generation, and (2) low interest among teenagers in learning local arts and cultural traditions.